(untitled) (Journal of Medicine, 2009)
Oxidative stress is currently suggested as mechanism underlying diabetes and diabetic complications. The aim of the study was to evaluate the magnitude of oxidative stress in patients with diabetes by measuring the lipid peroxidation as well as the status of the antioxidant defense system, thyroid hormones status and other biochemical variables. The study population consisted of 100 subjects divided into two groups viz. diabetic (n=50) and healthy controls (n=50). Changes in the levels of lipid peroxidation and antioxidants and thyroid hormones status were determined in diabetic and non-diabetic subjects. The level of thiobarbituric acid reactive substances (TBARS) was found to be increased significantly in diabetic patients compared to healthy controls. On the other hand, the activities of superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx), glutathione-S-transferase (GST), reduced glutathione (GSH), vitamin A, vitamin E and vitamin C were found to be decreased significantly in diabetics when compared to control subjects. We also noticed a marked increase in serum total cholesterol, triglyceride, low-density lipoprotein cholesterol (LDL-C), very low-density lipoprotein cholesterol (VLDL-C), and decrease in highdensity lipoprotein cholesterol (HDL-C), total protein and albumin in diabetic patients. The level of TSH was significantly decreased whereas the levels of T4 and FT4 were significantly increased in diabetic patients than the control subjects. However, the T3 and FT3 levels did not differ significantly between groups. Our findings indicate that changes in oxidant and antioxidant equilibrium will have biological and possibly pathological role in the development of secondary complications. It also demonstrate that detection of thyroid hormone status in the early stage of the disease will help the patients to improve quality of life and reduce the morbidity rate. Key Words: Diabetes mellitus, Oxidative stress, Lipid peroxidation, Antioxidant status, Thyroid hormones. doi: 10.3329/jom.v10i2.2816 J MEDICINE 2009; 10 : 60-66